2019
DOI: 10.1007/s43188-019-00003-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic evaluation of occupational exposure to antineoplastic drugs

Abstract: During the last years, several reports have provided evidence about adverse health effects on personal involved in Antineoplastic Drugs (ANPD) handling. ANPD has the ability to bind DNA, thus produce genotoxic damage. In this way, XRCC1 and XRCC3 proteins are necessary for efficient DNA repair and polymorphisms in this genes can be associated with an individual response to ANPD exposure. Therefore, the aim of this study was to evaluate genetic damage of occupational exposure to antineoplastic drugs and the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Several previous studies have assessed the effect of antineoplastic drug exposure on DNA damage by comet assay and CBMN assay with varying conclusions. Similar to our results, some studies from different countries have found a significant increase of DNA damage in subjects exposed to antineoplastic drugs as compared with control subjects 21–25. Moreover, a recent systematic review and meta-analysis demonstrated a clear and significant association between occupational exposure to antineoplastic drugs and the extent of primary DNA damage in health professionals 7.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have assessed the effect of antineoplastic drug exposure on DNA damage by comet assay and CBMN assay with varying conclusions. Similar to our results, some studies from different countries have found a significant increase of DNA damage in subjects exposed to antineoplastic drugs as compared with control subjects 21–25. Moreover, a recent systematic review and meta-analysis demonstrated a clear and significant association between occupational exposure to antineoplastic drugs and the extent of primary DNA damage in health professionals 7.…”
Section: Discussionsupporting
confidence: 91%
“…From the 21 articles read in full, 2 were excluded because they did not present comet assay data. Nineteen studies of occupational exposure [ 12 , 16 , 191 , 196 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ] remained for qualitative analysis, as summarised in Figure 3 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…2,4 The prevalence of micronuclei (DNA fragments) in epithelial cells and peripheral lymphocytes of healthcare workers exposed to cytotoxic drugs was also found to be statistically higher compared to controls. 3,5 There is also evidence to suggest that oxidative stress is increased in exposed professionals. 6 The International Society of Oncology Pharmacy Practitioners, 7 the Occupational Safety and Health Administration (OSHA) 8 and the American Society of Health-System Pharmacists 9 recommend that employers mandatorily ensure training before starting handling these drugs.…”
Section: Introductionmentioning
confidence: 99%